Phytoecological and Phytosociological Investigations of the Vegetation of Golcuk (Kocaeli/Turkey) - YARCI, CELAL; SEVEROĞLU, ZEKİ (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2012)
This study was conducted to determine the phytoecological and phytosociological characteristics of the vegetation which is distributed in Golcuk District (Kocaeli/Turkey) and put forward its syntaxonomy. Field studies has been carried out by using the classic Braun-Blanquet method in the years of 2005-2007. Two associations belonging to macchia vegetation and three associations belonging to forest vegetation were determined from the investigation area. Four of these associations are new and their description, typification and syntaxonomy has been done. Phytosociological and phytoecological features of these associations were discussed and compared to their relatives. The associations described arc as follows: Maquis vegetation, 1. Associations: Ferulago confusae-Quercetum cocciferae ass. nova 2. Associations: Erico arborae-Phillyretum latifoliae ass. nova Forest vegetation, 3. Associations: Carici serratulae-Quercetum ibericae ass. nova 4. Associations: Smilaco-Castanetum sativae Ketenoglu, Tug and Kurt 2010 5. Associations: Cardamino tenerae-Fagetum orientalis ass. nova
Keywords: Golcuk; Kocaeli; phytoecology; phytosociology; SYNTAXONOMY; FOREST